The importance of dyspnoea in the diagnosis of chronic obstructive pulmonary disease: a descriptive analysis of a stable cohort in Portugal (SAFE Trial) - Bárbara, C (2011)
INTRODUCTION: The aim of this study was to determine patient-perceived characteristics of chronic obstructive pulmonary disease (COPD) in patients participating in a large trial evaluating tiotropium bromide. PATIENTS AND METHODS: Baseline symptoms were assessed by means of a standardized questionnaire. Patients reported symptoms that led to diagnosis as well as their current most troublesome symptom. RESULTS: Data were obtained from 298 patients, mostly male (95%), with mean (standard deviation) baseline forced expiratory volume in 1 second of 1.1 (0.4) L (40.6 [13.3] % of predicted), mean disease duration of 14.4 (10.1) years and smoking history of 55.1 (25.3) pack-years. Dyspnoea was the most frequently reported symptom leading to COPD diagnosis (55.0% of patients), followed by cough (33.2%). Dyspnoea was also the current most troublesome symptom (82.6%), followed by cough (8.4%). The presence of dyspnoea or cough was independent of COPD severity. The most commonly reported co-morbidities were cardiovascular disorders (49% of patients), gastrointestinal disorders (20%) and metabolic disorders (16%), mainly diabetes mellitus. CONCLUSIONS: This analysis confirms the importance of dyspnoea as the most common symptom leading to initial COPD diagnosis and the symptom most troublesome to patients. Co-morbidities are common among COPD patients, and hence spirometric testing is appropriate in a patient who presents with dyspnoea associated with such a condition.